2010
DOI: 10.1161/circinterventions.109.918722
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion Grade After Late Infarct Artery Recanalization Is Associated With Global and Regional Left Ventricular Function at One Year

Abstract: Background Whether myocardial perfusion grade (MPG) following late recanalization of infarct-related arteries (IRA) predicts left ventricular (LV) function recovery beyond the acute phase of myocardial infarction (MI) is unknown. Methods and Results The Total Occlusion Study of Canada-2 (TOSCA-2) enrolled stable patients with persistently occluded IRA beyond 24 h and up to 28 days post-MI. We studied the relationship between the initial MPG and changes in LV function and volume, and the change in MPG from im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Whether improving infarct perfusion is beneficial to infarct healing and preventing myocardial remodeling remains to be determined in future studies. However, higher perfusion of the infarct has been shown to be associated with better myocardial recovery at the long‐term stage . Moreover, meta‐analysis of percutaneous coronary intervention studies targeting totally occluded infarct‐related artery reported that restoring the coronary flow at an average of 10 days after an MI is associated with improved cardiac function and reduced LV remodeling in the long‐term stages .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether improving infarct perfusion is beneficial to infarct healing and preventing myocardial remodeling remains to be determined in future studies. However, higher perfusion of the infarct has been shown to be associated with better myocardial recovery at the long‐term stage . Moreover, meta‐analysis of percutaneous coronary intervention studies targeting totally occluded infarct‐related artery reported that restoring the coronary flow at an average of 10 days after an MI is associated with improved cardiac function and reduced LV remodeling in the long‐term stages .…”
Section: Discussionmentioning
confidence: 99%
“…However, higher perfusion of the infarct has been shown to be associated with better myocardial recovery at the long-term stage. 24 Moreover, meta-analysis of percutaneous coronary intervention studies targeting totally occluded infarct-related artery reported that restoring the coronary flow at an average of 10 days after an MI is associated with improved cardiac function and reduced LV remodeling in the long-term stages. 25 These data suggest that increasing the infarct perfusion with mechanical LV unloading may be favorable for treating recent MI.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…It was not clear if the total blush was superior to the simple MPG. [ 1 ] Theoretically, the blush grade does not take into account the area of the blush. Therefore, the total blush should have been better.…”
Section: Discussionmentioning
confidence: 99%
“…The myocardial perfusion grade (MPG) is the measurement of coronary myocardial perfusion. [ 1 ] It primarily aims to quantify the increase in gray value over time. [ 2 ] The darker the myocardium, the better the perfusion is.…”
Section: Introductionmentioning
confidence: 99%
“…However, the earliest time that the recovery of dysfunctional but viable myocardium can be detected remains unknown. Conventional echocardiography enables us to identify significant left ventricular (LV) dysfunction but not subclinical dysfunction [10]. Two-dimensional speckle tracking echocardiography (2D-STE) allows for an angle-independent evaluation of myocardial strain, and provides comprehensive information on LV myocardial contractility.…”
Section: The Role Of Two-dimensional Speckle Tracking Echocardiographymentioning
confidence: 99%